Materials Science Practice study aid - Khvorova specialist in the field of materials science Senior Lecturer of Tomsk Polytechnic University; Egorov specialist in mechanical engineering The Head of the Laboratory of Tomsk Polytechnic University, candidate of technical Sciences; Kovalevskaya specialist in materials science Professor of Tomsk Polytechnic University, Doctor of Technical Sciences; Utyev specialist in the field of material science Senior Lecturer of Tomsk Polytechnic University (TPU Publishing House, 2012)
The study aid contains methodical instructions for laboratory works on discipline "Materials Science" and is intended for training students majoring in the direction 150700 "Mechanical engineering" in English. The laboratory practice is directed to intensification of theoretical knowledge in discipline and allows students to get practical skills of laboratory researches.